2021
DOI: 10.1016/j.jsxm.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes After Genital Gender-Affirming Surgery With Versus Without Urethral Lengthening in Transgender Men

Abstract: Background: In our institution, genital Gender-Affirming Surgery (gGAS;phalloplasty or metoidioplasty) in transgender men is offered with or without Urethral Lengthening (UL). Aim: The aim of this cross-sectional and retrospective study was to assess the effect of gGAS with or without UL on several Patient-Reported Outcomes (PROs), and to identify predictors of overall patient satisfaction at follow-up. Methods: A self-constructed Patient-Reported Outcome Measure (PROM) was sent to transgender men who were ≥1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The authors suggested that this may be due to increased erogenous sensation following metoidioplasty compared to phalloplasty, and patients’ acceptance that they are unlikely to acquire a phallus large enough for penetrative intercourse. 18 This finding further supports that erogenous sensation, the ability to orgasm, and erectile function appear to be more important than the ability to have penetrative intercourse for patients who have undergone metoidioplasty. These results can facilitate decision-making for patients who are exploring options in regard to bottom gender-affirmation surgery.…”
Section: Discussionsupporting
confidence: 62%
“…The authors suggested that this may be due to increased erogenous sensation following metoidioplasty compared to phalloplasty, and patients’ acceptance that they are unlikely to acquire a phallus large enough for penetrative intercourse. 18 This finding further supports that erogenous sensation, the ability to orgasm, and erectile function appear to be more important than the ability to have penetrative intercourse for patients who have undergone metoidioplasty. These results can facilitate decision-making for patients who are exploring options in regard to bottom gender-affirmation surgery.…”
Section: Discussionsupporting
confidence: 62%
“…We believe that a well-considered shared decision for or against UL will increase patient satisfaction postoperatively. In a previous study, comparable patient-reported outcomes were described after gGAS with and without UL, and satisfaction with the appearance of the neophallus and with voiding were positive predictors of overall satisfaction at follow-up, in contrast to the complication and reoperation rate, and independently of UL (de Rooij et al., 2021 ).…”
Section: Introductionmentioning
confidence: 73%
“…This difference in the number of men choosing for or against UL may be explained by the paradigm shift toward a more patient-centered care approach, in which all surgical options and their associated benefits and risks are presented and a definitive choice of treatment is made after extensive preoperative counseling and through shared decision-making (Elfering et al., 2017 ). It is thought that achieving the most suitable choice of gGAS for each individual will lead to the highest rates of satisfaction, and in the current situation of transgender care from a patient’s point of view, the need to void while standing appears to be much more variable with in our institution more men opting for gGAS without UL (de Rooij et al., 2021 ; Jacobsson et al., 2017 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations